Keefektifan fosfin formulasi cair terhadap Aphis gossypii Glover dan Macrosiphoniella sanborni Gillette (Hemiptera: Aphididae) pada bunga potong krisan - Nur Rachman; Dadang Dadang; R. Yayi Munara Kusumah (Jurnal Entomologi Indonesia, 2015)
Cut flower of chrysanthemum has high aesthetic and economic values. Export volume of chrysanthemums from Indonesia are lower than other countries, due to the impact of insect pest. Insect pests, Aphis gossypii Glover and Macrosiphoniella sanborni Gillette are currently associated with cut flowers especially chrysanthemum. One control measures usually taken in quarantine is fumigation. Alternative fumigant, liquified phosphine formulations may potentially be applied for quarantine treatment. The objectives of this study were to determine the concentration and exposure time of liquified phosphine against these species and to evaluate the effect of fumigant on the physical quality of cut flowers. The experiment was conducted in four steps: (1) identification and mass rearing of A. gossypii and M. sanborni; (2) preliminary tests on adult and third instar nymphs; (3) determination of liquified phosphine with various concentration and exposure time against adult and third instar nymphs of A. gosspypii and M. sanborni and; (4) validation test of effective concentration of fumigant and exposure time and the effect on quality of cut flowers. The results of study showed concentration of fumigant causing 100% mortality A. gossypii and M. sanborni  ere 500 ppm and 700 ppm, respectively with exposure time 12 hours. Concentrations of 700 ppm and exposure time up to 18 hours did not cause negative impact to the quality of chrysanthemum cut flowers.